solve for x.

-3(-4x - 3)=-27

1 answer

To solve the equation \(-3(-4x - 3) = -27\), we can start by simplifying the left side:

  1. Distribute \(-3\) to the terms inside the parentheses:

\[ -3 \cdot -4x - 3 \cdot -3 = 12x + 9 \]

Now the equation becomes:

\[ 12x + 9 = -27 \]

  1. Next, we isolate \(12x\) by subtracting \(9\) from both sides:

\[ 12x + 9 - 9 = -27 - 9 \] \[ 12x = -36 \]

  1. Finally, divide both sides by \(12\) to solve for \(x\):

\[ x = \frac{-36}{12} \] \[ x = -3 \]

Thus, the solution is:

\[ \boxed{-3} \]